Extensões dos modelos de sobrevivência referente a distribuição Weibull - Vigas, Valdemiro Piedade (Universidade Federal de São Carlos, 2014)
In this dissertation, two models of probability distributions for the lifetimes until the occurrence of the event produced by a specific cause for elements in a population are reviewed. The first revised model is called the Weibull-Poisson (WP) which has been proposed by Louzada et al. (2011a). This model generalizes the exponential-Poisson distributions proposed by Kus (2007) and Weibull. The second, called long-term model, has been proposed by several authors and it considers that the population is not homogeneous in relation to the risk of event occurence by the cause studied. The population has a sub-population that consists of elements who are not liable do die by the specific cause in study. These elements are considered as immune or cured. In relation to the elements who are at risk the minimum value of time of the event accurance is observed. In the review of WP the expressions of the survival function, quantile function, probability density function, and of the hazard function, as well the expression of the non-central moments of order k and the distribution of order statistics are detailed. From this review we propose, in an original way, studies of the simulation to analyze the paramenters of frequentist properties of maximum likelihood estimators for this distribution. And also we also present results related to the inference about the parameters of this distribution, both in the case in which the data set consists of complete observations of lifetimes, and also in the case in which it may contain censored observations. Furthermore, we present in this paper, in an original way a regression model in a form of location and scale when T has WP distribution. Another original contribution of this dissertation is to propose the distribution of long-term Weibull-Poisson (LWP). Besides studying the LWP in the situation in which the covariates are included in the analysis. We also described the functions that characterize this distribution (distribution function, quantile function, probability density function and the hazard function). Moreover we describe the expression of the moment of order k, and the density function of a statistical order. A study by simulation viii of this distribution is made through maximum likelihood estimators. Applications to real data set illustrate the applicability of the two considered models.
Keywords: Análise de sobrevivência; Dados censurados; Distribuição Weibull; Modelos de regressão; Fração de cura; Regressão log weibull-poisson; Longa duração; Survival analisys; Censored data; Weibull-Poisson distribution; Log Weibull-Poisson regression; Long-term; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA